THE EFFECT OF FINANCING ON ISLAMIC BANKING ASSETS WITH NON-PERFORMING FINANCE AS A MODERATING VARIABLE IN INDONESIA - Septa Diana Nabella; Yandra Rivaldo; Sumardin Sumardin; Robby Kurniawan; Sabri Sabri (Jurnal Ekonomi, 2023)
This research is a study using secondary data obtained from the official website of the Financial Services Authority (OJK). The data collected by the author starts from 2011 – September 2020. This study used the MRA (Moderated Regression Analysis) method. This study aims to determine whether there is a partial influence and how moderation forms on disbursed financing (PYD) on Islamic Banking Assets with Non-Performing Finance (NPF) as a moderating variable. The results of this study show that there is a partial influence of PYD variables on Islamic Banking Assets. This is evidenced by the acquisition of t count > t table (42,000 > 0.7111) and significant values of < α (0.000 < 0.05). Then the moderating variable in the form of Non-Performing Finance (NPF) can moderate the relationship between PYD and Islamic Banking Assets. This is evidenced by the acquisition of significance values in the third regression model (including interaction variables) obtained by 0.000 this significance value is smaller than α = 0.05 (0.000 < 0.05).